Relationship Between Job Satisfaction and Health of Hygienists in Lithuania - Gitana Rederiene; Yvonne Buunk-Werkhoven; Greta Aidukaite; Alina Puriene (Elsevier, 2022)
ABSTRACT: Objectives: This study aimed to determine the perceived musculoskeletal and psychological symptoms and job satisfaction of Lithuanian dental hygienists. Second, the study aimed to examine the relationships between job satisfaction and musculoskeletal and psychological symptoms amongst dental hygienists in Lithuania. Methods: A 41-item survey was sent by email to all members of the Lithuanian Dental Hygienists Association (N = 328) up to 3 times. The questionnaire comprised 5-point Likert scale structured questions, which were developed according to 3 existing questionnaires. Results: The final response rate was 52.4% (N = 172). The level of overall work-related physical health was 3.76 ± 0.65, and the most common physical health symptom was upper back pain; the level of overall work-related psychological health was 3.84 ± 0.64, and the most common symptom was stress. The level of overall job satisfaction was 3.87 ± 0.62, and the most satisfying areas were their relationships with colleagues, relationships with dentists, and working conditions (equipment, work environment); the least satisfying practice areas were income, work-related physical and psychological health, and social security. Conclusions: According to the results of this study, Lithuanian dental hygienists were quite satisfied with their job but sometimes experienced work-related musculoskeletal and psychological disorders. Their physical health score and the total psychological health score were significantly correlated with all job satisfaction criteria. The better the self-evaluation of physical and psychological health, the higher the job satisfaction reported.